Hippocampal involvement in safety signal learning varies with anxiety among healthy adults - Odriozola, Paola; Kribakaran, Sahana; Cohodes, Emily M.; Zacharek, Sadie J.; McCauley, Sarah; Haberman, Jason T.; Quintela, Lauren A.; Hernandez, Cristian; Spencer, Hannah; Prüßner, Luise; Caballero, Camila; Gee, Dylan G. (Biological psychiatry: global open science, 2024)
Background - Safety signal learning (SSL), based on conditioned inhibition of fear in the presence of learned safety, can effectively attenuate threat responses in animal models and humans. Difficulty regulating threat responses is a core feature of anxiety disorders, suggesting that SSL may provide a novel mechanism for fear reduction. Cross-species evidence suggests that SSL involves functional connectivity between the anterior hippocampus and the dorsal anterior cingulate cortex. However, the neural mechanisms supporting SSL have not been examined in relation to trait anxiety or while controlling for the effect of novelty. - Methods - Here, we investigated the neural mechanisms involved in SSL and associations with trait anxiety in a sample of 64 healthy (non-clinically anxious) adults (ages 18-30 years; 43 female, 21 male) using physiological, behavioral, and neuroimaging (functional magnetic resonance imaging) data collected during an SSL task. - Results - During SSL, compared with individuals with lower trait anxiety, individuals with higher trait anxiety showed less fear reduction as well as altered hippocampal activation and hippocampal-dorsal anterior cingulate cortex functional connectivity, and lower inferior frontal gyrus and ventrolateral prefrontal cortex activation. Importantly, the findings show that SSL reduces threat responding, across learning and over and above the effect of novelty, and involves hippocampal activation. - Conclusions - These findings provide new insights into the nature of SSL and suggest that there may be meaningful variation in SSL and related neural correlates as a function of trait anxiety, with implications for better understanding fear reduction and optimizing interventions for individuals with anxiety disorders.
Online veröffentlicht: 8. Juni 2023, Artikelversion: 16. Januar 2024
Gesehen am 08.04.2024